EVALUATION OF NATURAL FERMENTATION PROCESSES IN COCOA BEANS (THEOBROMA CACAO L.) AND SCREENING OF POTENTIAL ISOLATES AS STARTERS FOR COCOA FERMENTATION AT COCOA PLANTATIONS IN PALU, CENTRAL SULAWESI - Clarissa Budisarwono, Metta
As the world’s seventh-largest cocoa beans producer (650.600 tons in 2022), Indonesia predominantly exports dried cocoa beans rather than processed cocoa products. This happens due to the improper post-harvest, as seen in Palu, South Sulawesi, one of Indonesia’s main cocoa-producing regions. Palu produces cocoa with unpleasant taste and aroma thus affect the farmer’s walfare. Fermentation process is the important step in cocoa’s flavors formation, therefore comprehensive knowledge on the role of indigenous microbes is one of the necessary steps to ensure good quality cocoa beans. Microbial ecology using culture dependent approach was carried out to evaluate of cocoa bean’s natural fermentation in Palu, Central Sulawesi. The purposes of this project are: (1) to determine the quality of naturally fermented cocoa beans; (2) to determine the microbial population dynamics during natural fermentation process; (3) to determine the best isolates as a starter based on their enzymatic ability. The fermentation was carried out in Desa Bariri, Palu using a wooden fermenter measuring 40 x 40 x 50 cm³ on a 10 kg scale. Stirring was done every 2 days for 7 days with fermentation temperature of 25.8°C – 41.4°C and pulp’s pH 3.4 – 5.3. After fermentation, cocoa beans were dried directly under the sun for 3 days. Quantitative and qualitative analyses during natural fermentation are weight loss, number of beans in 100 grams, fermentation index, organoleptic assay by 10 semi-trained panelists, metabolites concentration (glucose, fructose, sucrose, ethanol, acetic acid, citric acid, and lactic acid), as well as the phenolic content. Microbial enumeration was carried out using several media NA (total bacteria), PDA (total yeast), MRSA (total LAB), and GYCA (total AAB) medium incubated for 24-48 hours at 37?. Followed by screening of enzymatic activities based on cellulolytic, pectinolytic, amylolytic, and proteolytic ability. Results gained from the natural-fermented cocoa beans analysis at the 7th day were (1) Grade A with 95 beans per 100 gram, (2) Fermentation index 80%, (3) Water content 11.9%, (4), Average score of sensory analysis 53.25%. Microbial growth dynamics began with yeast’s dominancy on day 0 to day 2 (1.9 x 106 CFU/ gram), followed by the growth of LAB from day 3 to 7 (1.8 x 109 CFU/ gram), and during the final days of fermentation was dominated by AAB from day 5 to day 7 (2.3 x 106 CFU/ gram). Microbial diversity were varied each day. During fermentation, concentration of glucose and fructose in the pulp decreased from 1376.7 mg/g pulp and 1866.9 mg/g pulp to undetectable levels, with average consumption rates of 744.9 mg/g pulp and 775.5 mg/g pulp per day, respectively. 23 microbial isolates were obtained (3 types of LAB, 4 types of yeast, 6 types of AAB, and 10 other aerobic bacteria). These siolates were then selected down to 2 isolates: 1 LAB isolate (T5M1) and 1 yeast isolate (T1P1). Both were used as starter candidates with cellulolytic, pectinolytic, amylolytic, and proteolytic enzymatic abilities. The growth profile results for isolate T5M1 showed a growth rate of 0.66/h and a generation time (GT) of 62.88 minutes in de Man Rogosa and Sharpe (MRS) medium incubated for 24 hours at 37°C. In contrast, isolate T1P1 exhibited a growth rate of 0.42/h and a GT of 99.1 minutes in Cocoa Pulp Simulator Medium (CPSM) incubated for 24 hours at 37°C with agitation at 150 rpm.